(a/a-5 - a/a+5 - a+25/25-a^2) * a-5/a+10a+25

+623 голосов
665k просмотров

(a/a-5 - a/a+5 - a+25/25-a^2) * a-5/a+10a+25


Алгебра (14 баллов) | 665k просмотров
Дан 1 ответ
+153 голосов

(

25−a

2

3

+

a

2

−10a+25

1

)∗

a

(5−a)

2

+

a+5

3a

=(

(5−a)

2

∗(a+5)

3∗(5−a)

+

(5−a)

2

∗(a+5)

1∗(a+5)

)∗

a

(5−a)

2

+

a+5

3a

=(

(5−a)

2

∗(a+5)

15−3a+a+5)

)∗

a

(5−a)

2

+

a+5

3a

=(

(5−a)

2

∗(a+5)

20−2a

)∗

a

(5−a)

2

+

a+5

3a

=(

(a+5)a

20−2a

)+

a+5

3a

=(

(a+5)a

20−2a+3a

2

)

(166 баллов)
+59

ух ё хаахах